The electronic elephant in the room: Physicians and the electronic health record. Issue 1 (11th June 2018) - Kroth, Philip J; Morioka-Douglas, Nancy; Veres, Sharry; Pollock, Katherine; Babbott, Stewart; Poplau, Sara; Corrigan, Katherine; Linzer, Mark
Abstract: Objectives: Determine the specific aspects of health information and communications technologies (HICT), including electronic health records (EHRs), most associated with physician burnout, and identify effective coping strategies. Materials and methods: We performed a qualitative analysis of transcripts from 2 focus groups and a burnout assessment of ambulatory physicians—each at 3 different health care institutions with 3 different EHRs. Results: Of the 41 clinicians, 71% were women, 98% were physicians, and 73% worked in primary care for an average of 11 years. Only 22% indicated sufficient time for documentation. Fifty-six percent noted "a great deal of stress" because of their job. Forty-two percent reported "poor" or "marginal" control over workload. Even though 90% reported EHR proficiency, 56% indicated EHR time at home was "excessive" or "moderately high." Focus group themes included HICT "successes" where all patients' information is accessible from multiple locations. HICT "stressors" included inefficient user interfaces, unpredictable system response times, poor interoperability between systems and excessive data entry. "Adverse outcomes" included ergonomic problems (eg, eye strain and hand, wrist, and back pain) and decreased attractiveness of primary care. Suggested "organizational changes" included EHR training, improved HICT usability, and scribes. "Personal/resilience" strategies focused on self-care (eg, exercise, maintaining work-life boundaries, and positive thinking). Discussion and conclusion: HICT use, while beneficial in many ways for patients and providers, has also increased the burden of ambulatory practice with personal and professional consequences. HICT and clinic architectural and process redesign are likely necessary to make significant overall improvements.